V/I control method and its an implementation for maximizing attainable efficiency of induction motor - Ramdan, Razali (2012)
Induction Motor (IM) drives are widely used in industrial, commercial, domestic, and other applications due to their simple robust construction, safe-long trouble free operation with minimum maintenance and wear and tear etc. Maximum efficiency of an IM usually occurs at near full load operation at rated 'voltage. But in many applications these motors are required to operate at other than rated load, where, the efficiency is much less than the maximum attainable efficiency. To achieve the maximum attainable efficiency at loads other than rated values, it is necessary to regulate the flux level by changing the voltage/frequency suitably at any given motor load. Large IMs usually are fairly highly efficient, compared to small TM. Low efficiency leads to uneconomic use of power in industrial installations. Maximum attainable efficiency operation of an IM at partial loads may be obtained by using a controller which can search for the maximum attainable efficiency condition at the given partial load and then operate the IM at that condition. The controllers reported in literature arrive at maximum efficiency point by minimizing the power or minimizing the current or maximizing power factor or optimizing the slip.